A kind of amino cellulose nanofiber and its preparation method and use
By first aminating and then nano-nomizing on cellulose, combined with step-by-step activation modification and the use of ε-polylysine, efficient aminolated nanocellulose was successfully prepared, solving the aminating modification in the prior art The problem of low sexual efficiency and complicated steps has achieved efficient preparation and excellent performance of amino cellulose nanocellulose.
Patent Information
- Application Number
- CN202211560404.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-12-06
AI Technical Summary
In the prior art, nanocellulose lacks antibacterial properties, which limits its wide application in the fields of biomedical and food engineering. The modification efficiency of nano-nanoization and then amino-aminoization is low, and the modification steps are complicated, making it difficult to achieve efficient amino-aminolated nano- Preparation of cellulose.
Using the strategy of first aminolation and then nano-nomization, by introducing carboxyl groups on cellulose and performing step-step activation modification, using 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N -hydroxysuccinimide is carried out for cross-linking reaction, combined with ε-polylysine as a high-density aminating reagent, to improve the aminating modification efficiency, and prepare aminocellulose nanofibers.
Achieve efficient preparation of amino-acided nanocellulose, with an amino content of up to 1.2mmol/g and a yield of 80%. It has excellent mechanical properties, fluorescence characteristics and antibacterial ability. It can be stable in both acidic and alkaline media, simplifying The preparation process is carried out and the reaction efficiency is improved.
Smart Images

Figure CN115976672B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer material and a preparation method and application thereof, and in particular to a preparation method, performance and application of aminocellulose nanofibers. Background Art
[0002] In recent years, nanocellulose has been widely used in biomedicine, biodegradable plastics and food engineering due to its high crystallinity, large specific surface area, good rheology, good biodegradability, good biocompatibility, easy derivatization and low toxicity. However, the lack of antibacterial properties of nanocellulose is one of the main difficulties limiting its widespread application. Inspired by the antibacterial mechanism of nanochitin and amine compounds, the preparation of nanocellulose containing amino groups and the construction of its antibacterial materials are very necessary to expand the application field of cellulose.
[0003] At present, the preparation of nanocellulose containing amino groups mainly adopts direct modification of nanocellulose, that is, nano-ization first and then amination. This method has the defects of low modification efficiency and cumbersome modification steps. If the strategy of amination first and then nano-ization is adopted, it is necessary to prepare amino cellulose first. At present, the preparation of amino cellulose mainly adopts chemical crosslinking, epoxy grafting, quaternary ammonium salt grafting and grafting modification under low eutectic solvent system. For example, researchers use epichlorohydrin to construct reactive intermediates, and give the cellulose surface epoxy structure through nucleophilic substitution reaction between active chlorine atoms and hydroxyl groups on the cellulose surface, and then prepare amino cellulose through polyethyleneimine amination ring-opening grafting reaction. The amino cellulose can be used as an adsorbent to remove / recover nitrates in aqueous solution. Wang et al. used carboxylated cellulose fiber as raw material, modified the residual hydroxyl groups on the cellulose surface with quaternary ammonium salt (2,3-epoxypropyltrimethylammonium chloride), and obtained zwitterionic nanocellulose under neutral conditions by high-pressure homogenization. Hong et al. used a DES system composed of betaine hydrochloride and glycerol to pre-treat cellulose and prepared cellulose nanofibers using microfluidization technology. The DES system can not only expand the fiber structure but also weaken the interaction of the hydrogen bond network. However, although betaine hydrochloride can react with the hydroxyl groups on the surface of cellulose to generate cationic nanocellulose, the degree of substitution is very small, which makes the cationic charge density of cellulose very low. In summary, due to the low efficiency of heterogeneous cellulose amination modification and the weak effect of the introduction of small molecule amination reagents on the surface charge density of cellulose, there is no report on the successful realization of cellulose nanofiberization by using the first amination modification strategy.
[0004] The present invention innovatively adopts the strategy of amination first and then nano-crystallization to achieve efficient preparation of amination nanocellulose. It is mainly through 1) introducing carboxyl groups on cellulose; 2) coordinating step-by-step activation modification to change the traditional one-pot cross-linking method of 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide, using a step-by-step activation method to convert the carboxyl groups on the surface of cellulose into cellulose O-acylurea reactive intermediate esters, centrifugally removing the carbodiimide that does not participate in the reaction, and then adding N-hydroxysuccinimide to react to generate cellulose intermediate esters that can react efficiently, thereby improving the efficiency of cellulose amination modification; 3) using macromolecular polylysine rich in high-density amino groups as an amination agent; on the one hand, it improves the efficiency of cellulose surface amination modification, and on the other hand, it increases the amino content on the surface of the amination cellulose, thereby achieving efficient preparation of amination nanocellulose. Summary of the invention
[0005] In view of the problems in the related art, the present invention proposes a preparation method of aminocellulose nanofibers, aminocellulose nanofibers and applications through innovation and optimization of the reaction process to overcome the above technical problems existing in the related art.
[0006] The specific invention principle is as follows: The mechanism of improving the efficiency of amino modification by step-by-step activation modification is: 1-(3-dimethyl-aminopropyl)-3-ethyl hydrochloride carbodiimide is a carbodiimide with the advantages of water solubility, non-cytotoxicity and biocompatibility; it can be safely and efficiently cross-linked with amino groups as coupling agents, and N-hydroxysuccinimide is used as a stabilizer to synergistically improve the cross-linking efficiency. The traditional approach is to use N-hydroxysuccinimide to convert the O-acylisourea intermediate generated by the reaction of the surface carboxyl group of the reactant and 1-(3-dimethyl-aminopropyl)-3-ethyl hydrochloride carbodiimide into a more stable and more active cellulose reactive intermediate ester. However, since O-acylisourea may also undergo transformation and rearrangement into other byproducts, such as anhydrides, hydrolyzed urea and carboxylic acids, etc. And the activation of carboxyl groups often requires excessive reaction, which may lead to side reactions, such as self-crosslinking between carboxyl groups, and the low reaction efficiency caused by the presence of excessive 1-(3-dimethyl-aminopropyl)-3-ethyl hydrochloride carbodiimide in the system, which may also reduce the further conversion of O-acylisourea to cellulose reactive intermediate esters. In view of this, the present invention innovatively adopts "step-by-step activation" to convert the carboxyl groups on the surface of carboxylated cellulose into cellulose reactive intermediate esters to reduce or avoid possible by-products and side reactions and improve the reaction efficiency. ε-polylysine is composed of 25 to 35 lysine residues and contains rich amino groups on the surface. It is a highly water-soluble, low-toxic, antibacterial, yeast and mold antibacterial drug. At the same time, ε-polylysine has cationic properties, edibility, water solubility, biodegradability, and non-toxicity, and can be used for drug delivery, water-absorbing hydrogels, bioadhesives, protein immobilization, antigen / antibody immobilization and wound dressings. Therefore, from the perspective of structure and function, ε-polylysine is undoubtedly a good raw material for preparing aminocellulose as an amination reagent rich in high-density amino groups.
[0007] To this end, the specific technical solution adopted by the present invention is as follows:
[0008] According to one aspect of the present invention, a green and efficient method for preparing amino-modified nanocellulose is provided, characterized in that it comprises the following steps:
[0009] (1) chemically pretreating cellulose to obtain a carboxylated cellulose raw material;
[0010] (2) under weak acid conditions, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide are added step by step to carboxylated cellulose to generate reactive cellulose intermediate esters by "stepwise activation" modification;
[0011] (3) the cellulose intermediate ester and ε-polylysine undergo an amidation reaction under weak alkaline conditions to obtain an amino-modified cellulose material;
[0012] (4) Amino cellulose nanofibers are obtained by mechanical treatment and separation and purification of amino-modified cellulose under acidic conditions.
[0013] Furthermore, the chemical pretreatment method in step (1) is at least one of TEMPO oxidation, oxalic acid oxidation, potassium permanganate oxidation and polyacid DES system pretreatment. Preferably, TEMPO oxidation is used, which can be TEMPO chemical oxidation and TEMPO enzymatic oxidation;
[0014] Furthermore, in step (1), the carboxyl content in the oxidized cellulose is 1.0-1.8 mmol / g.
[0015] Furthermore, in step (2), the carboxylated cellulose is first reacted with 1-ethyl-(3-dimethylaminopropyl) carbodiimide for 0.5-6 h to generate cellulose O-acylurea intermediate ester, and then the unreacted 1-ethyl-(3-dimethylaminopropyl) carbodiimide is removed after separation, and then N-hydroxysuccinimide is added to react for 1-6 h to efficiently generate reactive cellulose intermediate ester.
[0016] Furthermore, the pH of the weakly acidic condition in step (2) is 4-6; and the pH of the weakly alkaline condition in step (3) is 7.5-10.
[0017] Furthermore, the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide added in step (2) is 10-20 times the molar ratio of the carboxyl content of cellulose.
[0018] Furthermore, in step (3), the molecular weight of ε-polylysine is 2000-5000Da, and the concentration of ε-polylysine is 3mg / ml to 12mg / ml.
[0019] Furthermore, the yield of the aminocellulose nanofibers prepared in step (4) is 50-80%; and the amino content is 0.7-1.2 mmol / g.
[0020] According to another aspect of the present invention, an aminocellulose nanofiber is provided. The aminocellulose nanofiber has a length of 100-3000 nm and a diameter of 3-100 nm.
[0021] Furthermore, the surface of the aminocellulose nanofiber contains both carboxyl and amino groups, has an isoelectric point of pH 9-10, has amphoteric dispersion properties, and has stable dispersion properties in both acidic and alkaline media.
[0022] According to another aspect of the present invention, there is provided a method for preparing an aminocellulose nanofiber dispersion, comprising the following steps: dispersing the aminocellulose nanofibers in a dispersion medium, wherein the dispersion medium is at least one of water, ethanol, dimethyl sulfoxide, DMF, and DMAc, and the mass concentration of the dispersion is 0.01-10%.
[0023] According to another aspect of the present invention, a method for preparing aminocellulose nanofibers or aminocellulose nanofiber dispersion is provided, and the method is used in textile, pharmaceutical, food and daily chemical products.
[0024] Beneficial effects:
[0025] Compared with the prior art, the present invention has the advantages of high efficiency, mild reaction conditions, simple reaction process and no by-products, and the specific highlights are as follows:
[0026] (1) The traditional method of directly modifying the amino group on nanocellulose is changed to a method of first modifying and then nano-forming, which simplifies the preparation process of amino nanocellulose. The amino content of the amino nanocellulose is as high as 1.2 mmol / g, and the preparation yield of the amino nanocellulose is as high as 80%.
[0027] (2) The amino-modified nanocellulose prepared by the present invention has uniform size, contains both carboxyl and amino groups, has a wide pH dispersion range, can be efficiently dispersed in both acidic and alkaline media, and has good dispersion stability.
[0028] (3) The aminocellulose nanofibers prepared by the present invention have excellent mechanical properties, fluorescence properties, antibacterial ability and emulsification properties, which facilitate the value-added utilization of cellulose materials.
[0029] Description of the accompanying tables and graphs
[0030] Figure 1 The dispersion photos and zeta potential of aminocellulose nanofibers at different pH values in the dispersion;
[0031] Figure 2 Transmission electron microscopy images of aminocellulose nanofiber dispersion at different pH values;
[0032] Figure 3 This is the infrared spectrum of aminocellulose nanofiber material;
[0033] Figure 4 Fluorescence images of aminocellulose nanofiber dispersion, film, and sponge materials;
[0034] Figure 5 The stress-strain curve and Young's modulus diagram of aminocellulose nanofiber membrane;
[0035] Figure 6 To characterize the antibacterial ability of aminocellulose nanofibers.
[0036] Figure 7 To characterize the emulsification ability of aminocellulose nanofibers. DETAILED DESCRIPTION
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] According to an embodiment of the present invention, a preparation method and application of aminocellulose nanofibers are provided. Now, the present invention is further described in conjunction with the accompanying drawings and specific embodiments. According to the preparation method of aminocellulose nanofibers according to an embodiment of the present invention, the method comprises the following steps:
[0039] S1, chemically pretreating cellulose to obtain a carboxylated cellulose raw material;
[0040] The cellulose raw material is derived from animal, plant, microbial cellulose or bacterial cellulose.
[0041] In one embodiment, the experimental process of preparing carboxyl-modified cellulose by TEMPO oxidation includes TEMPO chemical oxidation and TEMPO enzymatic oxidation, and the selected enzyme treatment is laccase treatment. The chemical method used is TEMPO / NaClO / NaBr oxidation method, wherein the amount of the oxidizing agent NaClO can be 4mmol / g, 5mmol / g, 6mmol / g, 7mmol / g, 8mmol / g and 10mmol / g.
[0042] The oxalic acid oxidation method is used to prepare carboxylated cellulose. The concentration of the acid solution is 20% to 60% (w / w), and can be 20%, 30%, 40%, 50%, 60% (w / w). The treatment temperature is from room temperature to 100°C, and can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C or 100°C. The treatment time is 1 to 120 hours.
[0043] In the formic acid oxidation method for preparing carboxylated cellulose, the concentration of the acid solution is 80% to 98% (w / w), and can be 80%, 85%, 90%, 95% or 98% (w / w), and the treatment temperature is from room temperature to 100°C, and can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C or 100°C. The treatment time is 1 to 120 hours.
[0044] The carboxylated cellulose is prepared by potassium permanganate oxidation method, the mass ratio of potassium permanganate addition to cellulose is 1 to 2:1, which can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, the treatment temperature is from room temperature to 100°C, which can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C or 100°C. The treatment time is 1 to 120 hours.
[0045] In addition, the polyacid DES system pre-treats cellulose to prepare carboxylated cellulose, and the low eutectic solvent includes at least one of oxalic acid / choline chloride and citric acid / choline chloride. The treatment temperature is from room temperature to 120°C, and can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, or 120°C. The treatment time is 1 to 120 hours.
[0046] The carboxyl content of the prepared carboxylated cellulose may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.8 mmol / g.
[0047] like Figure 3 The infrared spectrum of the carboxylated cellulose with a carboxyl content of 1.3 prepared by the present invention is shown: the peak at 1600 cm-1 is attributed to the stretching vibration of -COONa on the carboxylated cellulose, indicating that carboxyl groups are introduced into cellulose.
[0048] S2, under weak acid conditions, sequentially adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide to the carboxylated cellulose to form a reactive cellulose intermediate ester by "step-by-step activation" modification;
[0049] In one embodiment, under weakly acidic conditions of pH 4-6, preferably pH 4, 4.5, 5, 5.5 and 6, the added amount of 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide is 10-20 times the molar ratio of the carboxyl content of cellulose, preferably 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20; first, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and cellulose are added for a reaction time of 0.5-6h, preferably 0.5h, 1h, 2h, 3h, 4h, 5h and 6h; then, N-hydroxysuccinimide is added to further react with the product, and the reaction time is 1-6h, preferably 1h, 2h, 3h, 4h, 5h and 6h.
[0050] S3, cellulose intermediate ester and ε-polylysine undergo amidation reaction under weak alkaline conditions to obtain amino-modified cellulose material.
[0051] In one embodiment, the weakly alkaline pH can be 7.5-10, preferably: 7.5, 7.8, 8, 8.5, 9 or 10. The molecular weight of polylysine is 2000-5000Da. The concentration of ε-polylysine is 3-12mg / ml. Preferably: 3mg / mL, 4mg / mL, 5mg / mL, 6mg / mL, 7mg / mL, 8mg / mL, 9mg / mL, 10mg / mL, 11mg / mL and 12mg / mL. The amino content of amino-modified cellulose is: 0.7-1.2mmol / g,
[0052] S4. Amino-modified cellulose is mechanically treated and separated and purified under acidic conditions to obtain amino cellulose nanofibers.
[0053] In one embodiment, the acidic condition has a pH of 3-5, preferably a pH of 3, 3.5, 4, 4.5 or 5. The mechanical treatment is selected from at least one of homogenization, ultrasonic treatment, colloid mill treatment, high-speed stirring, high-pressure homogenization, ultrafine grinding and microfluidization. It is preferably ultrasonic treatment, and the ultrasonic time is 10s to 1h, preferably 30s to 5min, and can be 10s, 30s, 1min, 5min, 10min, 30min, 1h. The yield of aminocellulose nanofibers is 50-80%.
[0054] Figure 1 The dispersion images and zeta potential of aminocellulose nanofibers at different pH values are shown. Aminocellulose nanofibers can be stably dispersed under acidic, neutral and alkaline conditions, and flocculate obviously at pH = 9, and then stably disperse at pH = 11, indicating that its isoelectric point is around pH 9. Furthermore, with the increase of pH, the zeta potential values at different pH values gradually decrease, and a breakthrough from positive charge to negative charge occurs at pH = 9-10. This once again proves that the isoelectric point of aminocellulose nanofibers is around 9-10, which is close to the isoelectric point of ε-polylysine.
[0055] Figure 2The transmission electron micrographs of aminocellulose nanofibers prepared when the reaction concentration of ε-polylysine is 9 mg / mL at different pH values (3, 9, 11). In the amino nanocellulose fiber dispersion, the mass concentration of the nanofibers is 0.01% to 10% (w / w), and the mass concentration of the nanofibers can be 0.01, 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 3%, 5%, 6%, 8%, 9% or 10% (w / w). The size range of nanofibers is: length of 100nm-3000nm, width of 3~100nm, the length can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1500nm, 2000nm, 2500nm or 3000nm, and the width can be 3nm, 5nm, 8nm, 10nm, 20nm, 40nm, 50nm, 60nm, 80nm, 90nm or 100nm.
[0056] At pH 3 and 11, the fibers were uniform single fibers due to the electrostatic repulsion between the protonated amino groups and the free carboxylic acid anions, further indicating that the aminocellulose nanofibers can be stably dispersed in acidic or alkaline dispersion media. At pH 9, the fibers were completely flocculated due to the weak surface charge and the electrostatic repulsion disappeared.
[0057] In addition, the amino-modified nanocellulose fibers can also be dispersed in ethanol, dimethyl sulfoxide, DMF or DMAc to form a stably dispersed nanodispersion liquid.
[0058] Figure 3 The infrared spectra of aminocellulose nanofibers prepared when the cellulose carboxyl content was 1.3 mmol / g and the reaction concentration of ε-polylysine was 3, 6 and 9 mg / mL. -1 The peak at 1640 cm-1 was attributed to the stretching vibration of -COONa on carboxylated cellulose, indicating that carboxyl groups were introduced into cellulose after oxidation. -1 and 1560cm -1 The NH bending vibrations of the primary amine and the CO stretching vibrations of the N-acetyl residue of amide I are related to these vibrations. -1 The absorption peak at 1738 cm -1 There is a peak at , which is the stretching vibration of -C=O on the ester bond formed by the reaction of amino and carboxyl groups. With the increase of ε-polylysine concentration, the typical bands of amide and primary amine are enhanced, indicating that ε-polylysine enters carboxylated cellulose through the covalent coupling reaction between its primary amine group and the carboxyl group on the surface of carboxylated cellulose.
[0059] Figure 4 These are fluorescence images of aminocellulose nanofiber nanodispersion, film and sponge. It can be seen that the fluorescence performance of unmodified nanocellulose is very weak, while after amination modification, the amino nanocellulose prepared in the present invention has excellent aggregation-induced emission fluorescence properties.
[0060] Figure 5 The stress-strain curve and Young's modulus of aminocellulose nanofiber membrane (ε-9PL-nTOCN) are shown in Figure 1. Nanocellulose (TOCN) prepared by TEMPO-mediated oxidation is used as a control. From the stress-strain curve of the film, it can be seen that the stress-strain values of the aminocellulose nanofiber membrane are enhanced. The Young's modulus measured at a strain rate of 0.5% also gradually increases, and is consistent with the increasing trend of tensile strength. According to the data in the table, it is about twice that of the TOCN film.
[0061] Figure 6 The antibacterial ability of aminocellulose nanofibers (ε-9PL-nTOCN) is characterized. According to the plate count histogram, the antibacterial ability of aminocellulose nanofibers can reach more than 99% compared with the colony formation of the control group. This shows that after amino modification, nanocellulose can be endowed with excellent antibacterial properties.
[0062] Figure 7 The photos and microscope images of the high internal phase emulsions emulsified with the prepared aminocellulose nanofibers (ε-9PL-1.6TOCN) at different oil phase ratios (66%, 74% and 82%). The photos of the high internal phase emulsions emulsified with ε-9PL-1.6TOCN at different oil phase ratios (66%, 74% and 82%) and the stability photos of the high internal phase emulsions containing 82% oil phase after storage for 1, 7 and 30 days show that no phase separation and stratification occurred. However, the stable emulsion of TOCN (control group) was unstable, and obvious demulsification was observed after 1 day of storage. Therefore, the introduction of ε-polylysine improves the emulsification properties of cellulose. The droplets of the stable high internal phase emulsion of ε-9PL-1.6TOCN obtained by optical microscopy are closely arranged and uniform in size.
[0063] The following uses multiple groups of specific examples to describe in detail the preparation method of amino nanocellulose:
[0064] Example 1
[0065] a. Preparation of TEMPO chemical carboxylated cellulose:
[0066] Weigh 5g of dry weight cellulose and disperse it in 500ml of water, then add 0.5g of sodium bromide and 0.064g of TEMPO, stir to fully dissolve the components, then add 25mmol of sodium hypochlorite to the system, immediately adjust the pH to 10 with hydrochloric acid, and then continuously add 0.05mol / l of sodium hydroxide solution to maintain the system pH at 10. When the system no longer consumes sodium hydroxide, the mixed solution is centrifuged and washed, and the solid content of the washed TEMPO oxidized cellulose product is measured.
[0067] b. Preparation of carboxylated cellulose by TEMPO enzymatic method;
[0068] Weigh a certain amount of TEMPO and dissolve it in 0.1M pH 4.5 acetic acid-sodium acetate buffer to prepare a 5-70mM TEMPO solution. Take 1g of cellulose raw material and add it to a beaker containing 100mL of TEMPO solution. After stirring evenly, add 300-800U of laccase. Seal the beaker with plastic wrap and poke about 10 small holes in the plastic wrap with a fine needle to allow oxygen in the air to enter. Place the mixed system in a 25℃ water bath and stir it magnetically at 500rpm to start oxidation. After 8-140h of oxidation, place the mixed system in an ice water bath to cool for 30min to terminate the reaction. Wash the carboxylated cellulose with distilled water. The water-insoluble part obtained is TEMPO / laccase / O2 carboxylated cellulose (TLO-HBKP), which is stored in a 4℃ refrigerator.
[0069] c. Preparation of carboxylated cellulose by oxalic acid oxidation method:
[0070] 1 g of pulp was added to a reactor containing 50 mL of oxalic acid (50% (w / w)) and the reaction was carried out at 90°C and constant stirring at 250 rpm. Afterwards, the solution was filtered and the pulp was washed with hot water to avoid acid crystallization, and then filtered and washed with water at room temperature.
[0071] d. Formic acid oxidation method:
[0072] Cellulose was heated to 100°C in a formic acid solution (concentration 80% (w / w)) and stirred for 6 h. To promote the reaction process, 8 wt% FeCl3 was added as a catalyst. After the reaction was completed, the sample was immediately centrifuged and washed to neutrality.
[0073] e. Potassium permanganate oxidation method:
[0074] 1 wt% dilute sulfuric acid was poured into a three-necked flask, cellulose pulp and potassium permanganate were added into the flask at a mass ratio of 1:1.4 under stirring, heated and reacted for 6 hours, and then hydrogen peroxide was added to quench the reaction. The suspension was filtered and washed with deionized water to obtain carboxyl-modified cellulose.
[0075] f. Pretreatment of cellulose with polyacid DES system:
[0076] F-DES was prepared by stirring choline chloride and formic acid at a molar ratio of 1:2 in a round-bottom flask at 150 rpm at room temperature (25°C) for 30 minutes to obtain a transparent liquid of F-DES. Then, cellulose slurry was added to the F-DES, and the fiber consistency was 5wt%. The reaction was carried out in an oil bath at 90°C for a certain period of time. Afterwards, the dispersion was centrifuged to separate the supernatant and the solid residue. The solid residue was washed by centrifugation with 1000g of deionized water for 5 times, and then a pretreated carboxylated cellulose sample was obtained. In addition, the low eutectic solvent system can also include oxalic acid / choline chloride and citric acid / choline chloride.
[0077] By changing the above chemical modification conditions, a carboxylated cellulose raw material with a carboxyl content of 1.0-1.8 mmol / g can be obtained.
[0078] Example 2
[0079] (1) Taking the modification of carboxylated cellulose (TOC) with a carboxyl content of 1.6 mmol / g in Example 1 as an example, first, 1 g of dried TOC was added to 100 mL of deionized water and stirred to be uniformly suspended under magnetic stirring. The carboxylated cellulose was modified with a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:20:20; specifically, 6.15 g (32 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide was added under magnetic stirring. The obtained mixture was stirred at room temperature for 0.5-6 h, and the pH was dynamically maintained at 5.5-6. The excess 1-ethyl-(3-dimethylaminopropyl) carbodiimide was removed by centrifugation and washing to obtain a cellulose O-acylurea intermediate ester suspension.
[0080] (2) Add 3.69 g (32 mmol) of N-hydroxysuccinimide (100 mL system) to the suspension described in (1), and continue stirring at room temperature at pH 6 for 1-6 hours to obtain a cellulose intermediate ester suspension having a reaction activity.
[0081] (3) Dissolve 9 mg / mL ε-polylysine in the suspension described in (2), adjust the pH to 7-8, react under magnetic stirring at room temperature for 24 hours, and wash several times to obtain an amino-modified cellulose material.
[0082] (4) The amino-modified cellulose material is subjected to high-pressure homogenization treatment under acidic conditions to obtain an amino-cellulose nanofiber dispersion.
[0083] In this embodiment, the yield of aminocellulose nanofibers is 76.18±4.15%, the length of the nanofibers is about 502.87±274.06 nm, the diameter is 16.24±7.38 nm, and the amino content is 1.04±0.23 mmol / g.
[0084] The following Examples 3-5 use carboxylated cellulose with different carboxyl contents as the raw materials for amino modification, and the corresponding amounts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are also changed accordingly, to further illustrate the effect of carboxyl content on the efficiency of amino modification.
[0085] Example 3
[0086] (1) The experimental implementation process is the same as that of Example 2, except that the raw material used is carboxylated cellulose with a carboxyl content of 1.3 mmol / g. First, 1 g of dried TOC is added to 100 mL of deionized water and stirred under magnetic stirring to uniformly suspend. The carboxylated cellulose is modified with a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:20:20 respectively; specifically, 5 g (26 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide is added under magnetic stirring. The obtained mixture is stirred at room temperature for 0.5-6 h, and the pH is dynamically maintained at 5.5-6. The excess 1-ethyl-(3-dimethylaminopropyl) carbodiimide is removed by centrifugation and washing to obtain a cellulose O-acylurea intermediate ester suspension.
[0087] (2) Add 3 g (26 mmol) of N-hydroxysuccinimide (100 mL system) to the suspension described in (1), and continue stirring at room temperature at pH 6 for 1-6 hours to obtain a cellulose intermediate ester suspension having a reaction activity.
[0088] The experimental procedures of (3) and (4) are the same as those of Example 2.
[0089] In this embodiment, the yield of aminocellulose nanofibers is 65.92±4.01%, the length of the nanofibers is about 896.57±365.62 nm, the diameter is 25.93±9.85 nm, and the amino content is 0.82±0.03 mmol / g.
[0090] Example 4
[0091] (1) Example 2 The experimental implementation process is the same, except that the raw material used is oxidized cellulose with a carboxyl content of 1.0 mmol / g. First, 1 g of dried TOC is added to 100 mL of deionized water and stirred under magnetic stirring to uniformly suspend. The oxidized cellulose is modified with a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:20:20 respectively; specifically, 3.85 g (20 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide is added under magnetic stirring. The obtained mixture is stirred at room temperature for 0.5-6 h, and the pH is dynamically maintained at 5.5-6. The excess 1-ethyl-(3-dimethylaminopropyl) carbodiimide is removed by centrifugation and washing to obtain a cellulose O-acylurea intermediate ester suspension.
[0092] (2) Add 2.3 g (20 mmol) of N-hydroxysuccinimide (100 mL system) to the suspension described in (1), and continue stirring at room temperature at pH 6 for 01-6 h to obtain a cellulose intermediate ester suspension having a reaction activity.
[0093] The experimental procedures of (3) and (4) are the same as those of Example 2.
[0094] In this embodiment, the yield of aminocellulose nanofibers is 57.26±2.80%, the length of the nanofibers is about 1028.71±503.94 nm, the diameter is 27.83±11.3 nm, and the amino content is 0.73±0.04 mmol / g.
[0095] Example 5
[0096] (1) Example 2 The experimental implementation process is the same, except that the raw material used is carboxylated cellulose with a carboxyl content of 1.8 mmol / g. First, 1 g of dried TOC is added to 100 mL of deionized water and stirred under magnetic stirring to uniformly suspend. The carboxylated cellulose is modified with a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:20:20 respectively; specifically: 6.92 g (36 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide is added under magnetic stirring. The obtained mixture is stirred at room temperature for 0.5-6 h, and the pH is dynamically maintained at 5.5-6. The excess 1-ethyl-(3-dimethylaminopropyl) carbodiimide is removed by centrifugation and washing to obtain a cellulose O-acylurea intermediate ester suspension.
[0097] (2) Add 4.15 g (36 mmol) of N-hydroxysuccinimide (100 mL system) to the suspension described in (1), and continue stirring at room temperature at pH 6 for 1-6 hours to obtain a cellulose intermediate ester suspension having a reaction activity.
[0098] The experimental procedures of (3) and (4) are the same as those of Example 2.
[0099] In this embodiment, the yield of aminocellulose nanofibers is 80.28±3.01%. The length of the nanofibers is about 481.32±196.08 nm, the diameter is 12.42±5.68 nm, and the amino content is 1.2±0.25 mmol / g.
[0100] According to the experimental results of Examples 2-5, it can be concluded that the TOC with a higher degree of oxidation provides more carboxyl reaction sites, has a higher reaction activity, and has a higher yield and amino content of nanofibers.
[0101] The embodiments involved in the present invention are not limited to the above embodiments. Table 1 briefly lists the preparation method of an aminocellulose nanofiber involved in the present invention. Sequence numbers 1-16 are based on Example 2, and the effects of the amount of activating agent, oxidation method, carboxyl content, amount of polylysine and the addition method of the activating agent on the amino content and nano-yield of the modified aminocellulose are investigated. Sequence numbers 1-2 and 17-18 are based on Comparative Example 3, and the effects of the addition method of the activating agent on the amino content and nano-yield of the modified aminocellulose are investigated.
[0102] Table 1 Amino content and nano-yield of amino cellulose prepared under different conditions
[0103]
[0104] As shown in Table 1, the amino content and nano-size yield of aminocellulose prepared under some different conditions are shown. Here, we use examples and comparative examples to compare the amino content and nano-size yield to illustrate the influence of the research method on amination and nano-size, but not all examples and comparative examples are listed. ε-polylysine grafted cellulose successfully modifies part of the carboxylated cellulose under multiphase reaction conditions. The grafted amino-rich carboxylated cellulose is dispersed in an acidic system to obtain aminocellulose nanofibers; otherwise, the ungrafted or insufficiently grafted carboxylated cellulose cannot be nano-dispersed under acidic conditions. The yield of aminocellulose nanofibers is closely related to the carboxyl content in the carboxylated cellulose, the molar ratio of 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide, the reaction steps of carboxyl activation and the ε-polylysine concentration. As can be seen from Table 1, using the one-step carboxyl activation reaction step, when the carboxyl group of carboxylated cellulose is 1.6 mmol / g, the concentration of ε-polylysine is 3 mg / mL, and the molar ratio of carboxylated cellulose carboxyl group: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide is 1:20:20, the amino content and nano-yield of aminocellulose are 0.79±0.12 mmol / g and 60.18±3.12%, respectively, which are much higher than the amino content and nano-yield of aminocellulose corresponding to the molar ratio of 1:10:10, 0.68±0.09 mmol / g and 52.09±4.84%, and only slightly lower than 0.81±0.31 mmol / g and 63.98±4.92% at 1:20:40. Therefore, the molar ratio of 1:20:20 is used to further optimize the reaction. The higher the degree of oxidation of carboxylated cellulose, the more carboxyl reaction sites it provides and the higher the reaction activity: when the carboxyl content is 1.8 mmol / g and the ε-polylysine content is 9 mg / ml, the amino content can reach 1.2±0.25 mmol / g, and the ε-9PL-1.6TOCN nanofiber yield is 80.28±3.01%. Under the same reaction conditions, when the carboxyl content is 1.0 mmol / g, the amino content of the obtained aminocellulose is 0.73±0.04 mmol / g; the nanofiber yield is 57.26±2.80%. As mentioned above, ungrafted or insufficiently grafted carboxylated cellulose cannot be nanofibrillated under acidic conditions.In addition, with the increase of carboxyl content and ε-polylysine concentration, the more reactive functional groups there are, the higher the grafting rate and the corresponding amino content are also higher: taking carboxylated cellulose with a carboxyl content of 1.6 as an example, with the gradual increase of ε-polylysine concentration, the amino contents of the modified aminocellulose are 0.79±0.12mmol / g (3mg / mL), 0.90±0.03mmol / g (6mg / mL), 1.04±0.23mmol / g (9mg / mL) and 1.1±0.18 (12mg / mL), respectively; the yields of nanocellulose nanofibers are 60.18±3.12 (3mg / mL), 68.84±4.76 (6mg / mL), 76.18±4.15 (9mg / mL) and 79.46±2.74 (12mg / mL), respectively. For ε-3PL-1.6TOCN, when the molar ratio is 1:10:10 and 1:20:20, it can be seen from Table 1 that under the same conditions, the amino content and nano-yield of aminocellulose after "step-by-step activation" modification are higher than those of the carboxyl activation reaction of the one-step mixing method. This is because the activation of carboxyl groups by 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide requires too many reaction reagents. Due to the excess of 1-ethyl-(3-dimethylaminopropyl) carbodiimide in the system, the reaction efficiency is low, and side reactions such as self-crosslinking between carboxyl groups may occur, which reduces the further conversion of O-acylisourea to N-hydroxysuccinimide ester. Therefore, the "step-by-step activation" modification is conducive to the effective generation of O-acylisourea and its conversion into N-hydroxysuccinimide, which is crucial for the reaction between cellulose and ε-polylysine. It can be seen from this that: different oxidation methods for preparing carboxylated cellulose have little effect on the final amination efficiency and nano-yield; the step-by-step method can effectively improve the amination efficiency, and then increase the yield of amino cellulose nanofibers, which is the key to preparing aminized nanocellulose; the higher the cellulose carboxyl content, the more conducive it is to amination modification, and the higher the concentration of ε-polylysine, the more conducive it is to amination modification.
[0105] Comparative Example 1
[0106] (1) Example 2 The experimental implementation process is the same, except that the raw material used is carboxylated cellulose with a carboxyl content of 0.8 mmol / g. First, 1 g of dried TOC is added to 100 mL of deionized water and stirred under magnetic stirring to uniformly suspend. The carboxylated cellulose is modified with a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:20:20 respectively; specifically, 3.04 g (16 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide is added under magnetic stirring. The obtained mixture is stirred at room temperature for 0.5-6 h, and the pH is dynamically maintained at 5.5-6. The excess 1-ethyl-(3-dimethylaminopropyl) carbodiimide is removed by centrifugation and washing to obtain a cellulose O-acylurea intermediate ester suspension.
[0107] (2) Add 1.84 g (16 mmol) of N-hydroxysuccinimide (100 mL system) to the suspension described in (1), and continue stirring at room temperature at pH 6 for 1-6 hours to obtain a cellulose intermediate ester suspension having a reaction activity.
[0108] The experimental procedures of (3) and (4) are the same as those of Example 2.
[0109] In this embodiment, the yield of aminocellulose nanofibers is 40.72±3.98%, and the amino content is 0.49±0.05mmol / g. Therefore, the carboxyl content of cellulose is insufficient, and after further amino modification, it is not possible to obtain a high-yield nanofiber dispersion through nano-crystallization.
[0110] Comparative Example 2:
[0111] The experimental implementation process of Example 2 is the same, except that the ε-polylysine dissolved in the suspension described in step (3) is 2 mg / mL. In this example, the yield of aminocellulose nanofibers is 46.34±4.89%, and the amino content is 0.51±0.08 mmol / g. Therefore, the amination modification reagent is insufficient, and after further amination modification, a high-yield nanofiber dispersion cannot be obtained by nano-ization.
[0112] Comparative Example 3
[0113] (1) Taking the modification of carboxylated cellulose (TOC) with a carboxyl content of 1.6 mmol / g in the embodiment as an example, first, 1 g of dried TOC was added to 100 mL of deionized water and stirred under magnetic stirring to be uniformly suspended. The carboxylated cellulose was modified with a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:10:10; specifically, 2.5 g (13 mmol) of 1-ethyl-(3-dimethylaminopropyl) carbodiimide and 1.5 g (13 mmol) of N-hydroxysuccinimide (100 mL system) were added under magnetic stirring, and stirring was continued for 1-6 h at room temperature at pH 6 to obtain a cellulose intermediate ester suspension with reactive activity.
[0114] The experimental process of (3) and (4) is the same as that of Example 2. In this example, the yield of aminocellulose nanofibers is 19.22±3.13%, and the amino content is 0.20±0.04mmol / g.
[0115] Comparative Example 4
[0116] The implementation process is the same as that of Comparative Example 3, except that the carboxylated cellulose is modified by using a molar ratio of carboxyl: 1-ethyl-(3-dimethylaminopropyl) carbodiimide: N-hydroxysuccinimide of 1:20:20; in this example, the yield of aminocellulose nanofibers is 28.56±4.08%, and the amino content is 0.32±0.03mmol / g.
[0117] In summary, Comparative Examples 3 and 4, combined with Table 1, the results show that the reaction efficiency of step-by-step activation is better than that of one-pot cross-linking, because the activation of carboxyl groups by 1-ethyl-(3-dimethylaminopropyl)carbodiimide reaction and N-hydroxysuccinimide requires too many reaction reagents. Due to the excess of 1-ethyl-(3-dimethylaminopropyl)carbodiimide in the system, the reaction efficiency is low, and side reactions such as self-crosslinking between carboxyl groups may occur, which reduces the further conversion of O-acylisourea to cellulose reaction intermediate esters, making the reaction efficiency low. Therefore, step-by-step activation is conducive to the effective generation of O-acylisourea and its conversion into cellulose reaction intermediate esters, which is crucial for further mediating the reaction between cellulose and ε-polylysine.
Claims
1. A method for preparing aminocellulose nanofibers, characterized in that: The steps include: (1) chemically pretreating cellulose to obtain a carboxylated cellulose raw material having a carboxyl content of 1.0-1.8 mmol / g; (2) Under weak acid conditions, 1-ethyl-(3-dimethylaminopropyl) carbodiimide is first added to the carboxylated cellulose to react for 0.5-6 hours to generate a cellulose O-acylurea intermediate ester, and then the unreacted 1-ethyl-(3-dimethylaminopropyl) carbodiimide is removed after separation, and then N-hydroxysuccinimide is added to react for 1-6 hours to efficiently generate a reactive cellulose intermediate ester; (3) the cellulose intermediate ester and ε-polylysine undergo an amidation reaction under weak alkaline conditions to obtain an amino-modified cellulose material; (4) amino-modified cellulose is mechanically treated and separated and purified under acidic conditions to obtain amino cellulose nanofibers; In the step (1), the chemical pretreatment method is at least one of TEMPO oxidation, oxalic acid oxidation, potassium permanganate oxidation and polyacid DES system pretreatment; in the step (2), the added amounts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are both 10-20 times the molar ratio of the cellulose carboxyl content; in the step (3), the molecular weight of ε-polylysine is 2000-5000Da, and the concentration of ε-polylysine is 3-12mg / ml.
2. The method for preparing aminocellulose nanofibers according to claim 1, characterized in that: The pH of the weakly acidic condition in step (2) is 4-6; the pH of the weakly alkaline condition in step (3) is 7.5-10.
3. The method for preparing aminocellulose nanofibers according to claim 1, characterized in that: The yield of the aminocellulose nanofibers prepared in step (4) is 50-80% and the amino content is 0.7-1.2 mmol / g.
4. An aminocellulose nanofiber, characterized in that: The aminocellulose nanofiber is prepared by the preparation method of the aminocellulose nanofiber according to any one of claims 1 to 3; the aminocellulose nanofiber has a length of 100-3000nm and a diameter of 3-100nm.
5. The aminocellulose nanofiber according to claim 4, characterized in that The surface of aminocellulose nanofibers contains both carboxyl and amino groups, with an isoelectric point of pH 9-10. It has amphoteric dispersion properties and has stable dispersion properties in both acidic and alkaline media.
6. A method for preparing an aminocellulose nanofiber dispersion, characterized in that: The aminocellulose nanofibers according to claim 4 are dispersed in a dispersion medium, wherein the dispersion medium is at least one of water, ethanol, dimethyl sulfoxide, DMF, and DMAc, and the mass concentration of the dispersion liquid is 0.01-10%.
7. Use of the preparation method of the aminocellulose nanofiber according to claim 4 or 5 or the aminocellulose nanofiber dispersion according to claim 6 in textile, pharmaceutical, food and daily chemical products.
Citation Information
Patent Citations
Aminated nano cellulose crystal and preparation method thereof
CN105646722A
Microbial cellulose nanofibers for transducing biomolecules using radiation and manufacturing method thereof
KR1020140048362A